Thermodynamic analysis of Mn-As-H2O, Mn- Sb-H2O, Mn-Bi-H2O systems - Omarov, K.B.; Aldabergenova, S.K.; Absat, Z.B.; Rakhimzhanova, Z.; Siyazova, A.B. (My University, 2016)
Abstract—A thermodynamic analysis of Mn-As-H2O, Mn-Sb- H2O, Mn-Bi-H2O systems was made through calculation and drawing diagrams of E-pH, where the boundaries of the area of sustainability and formation of arsenates, antimonates and bismuthates of manganese are clearly shown.
Keywords: Antimony; arsenic; bismuth; diagram of the E-pH